Okara-based Product Processing as an Applicative Educational Tools for Junior High School Students in East Jakarta: Pengolahan Produk Pangan Berbasis Okara sebagai Sarana Pembelajaran Aplikatif pada Siswa Sekolah Menengah Pertama di Jakarta Timur - Desak Dewi; Kenneth Francis Wibisono; Hanny Angrainy; Wieke Windelyn; Colin Logan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Practical learning is one method that can improve students' understanding of a cause and effect concept through direct experience. Although there are already several practical learning activities through craft classes, schools generally still have obstacles in implementing them directly. One topic that can be used is okara-based food product processing. This community service program aims to provide socialization about healthy, safe, and nutritious food and facilitate students in applied learning in the field of food processing. The stages of the activity consist of counseling, training, technology application, mentoring and evaluation. Healthy, safe and nutritious food counseling activities increase students' knowledge. Students have also succeeded in making okara bar and okara noodle products, and explaining the scientific processes that occur due to differences in recipes, through direct practice and class presentations. To ensure the sustainability of the program, a food processing laboratory was established at SMP Mekar Sari. With this laboratory, teachers and students can be creative in making nutritious and safe processed foods and initiate entrepreneurship programs at school. This activity is expected to not only improve their knowledge and practical skills, but also raise awareness about the importance of consuming balanced and clean nutritious food so that it is beneficial for the body.